2019
DOI: 10.1051/0004-6361/201935034
|View full text |Cite
|
Sign up to set email alerts
|

Highly structured disk around the planet host PDS 70 revealed by high-angular resolution observations with ALMA

Abstract: Context. Imaged in the gap of a transition disk and found at a separation of about 195 mas (∼22 au) from its host star at a position angle of about 155 o , PDS 70 b is the most robustly detected young planet to date. This system is therefore a unique laboratory for characterizing the properties of young planetary systems at the stage of their formation. Aims. We aim to trace direct and indirect imprints of PDS 70 b on the gas and dust emission of the circumstellar disk in order to study the properties of this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
196
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(241 citation statements)
references
References 91 publications
33
196
2
Order By: Relevance
“…Here, we estimate the contribution of the unseen dust to the extinction. Keppler et al (2019) conducted hydrodynamic simulations to reproduce the observed 12 CO (2-1) integrated intensity map and found that the azimuthally averaged gas surface density at the location of PDS 70b is ∼0.01 g cm −2 , which can be translated to a molecular hydrogen surface density of ∼3 × 10 21 cm −2 . By using the relationship between the interstellar dust extinction and the hydrogen column density (N H /A V = 1.9 × 10 21 cm −2 mag −1 ; Bohlin et al 1978), we derived A V ∼ 3.3 mag, which corresponds to A Hα ∼ 2.4 mag with A λ ∝ λ −1.75 (Draine 1989), where we assume that hydrogen atoms are in the form of hydrogen molecules.…”
Section: Origin Of Planetary Extinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we estimate the contribution of the unseen dust to the extinction. Keppler et al (2019) conducted hydrodynamic simulations to reproduce the observed 12 CO (2-1) integrated intensity map and found that the azimuthally averaged gas surface density at the location of PDS 70b is ∼0.01 g cm −2 , which can be translated to a molecular hydrogen surface density of ∼3 × 10 21 cm −2 . By using the relationship between the interstellar dust extinction and the hydrogen column density (N H /A V = 1.9 × 10 21 cm −2 mag −1 ; Bohlin et al 1978), we derived A V ∼ 3.3 mag, which corresponds to A Hα ∼ 2.4 mag with A λ ∝ λ −1.75 (Draine 1989), where we assume that hydrogen atoms are in the form of hydrogen molecules.…”
Section: Origin Of Planetary Extinctionmentioning
confidence: 99%
“…A good example of robustly detected accreting planets at tens of au from a central star is the PDS 70 planetary system. This system includes a weakly accreting young star (spectral type of K7, mass of 0.8 M ⊙ , accretion rate of 6 × 10 −11 M ⊙ yr −1 , age of 5 Myr, distance of 113 pc; Pecaut & Mamajek 2016;Keppler et al 2019;Haffert et al 2019;Müller et al 2018;Gaia Collaboration et al 2018) associated with two planetary-mass companions (Haffert et al 2019;Isella et al 2019;Christiaens et al 2019a,b;Keppler et al 2018;Müller et al 2018;Wagner et al 2018). Aoyama & Ikoma (2019) estimated that PDS 70b's mass and mass accretion rate are ∼12 M Jup and ∼4 × 10 −8 M Jup yr −1 , respectively, while the values for PDS 70c are ∼10 M Jup and ∼1 × 10 −8 M Jup yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The posterior medians are listed in Table 5, with error bars calculated from the 16th and 84th percentiles. As noted in Keppler et al (2019), the nominal error bars should be regarded with caution because there may also be systematic uncertainties associated with image-plane fitting and differences between the assumed model structure and true emission behavior.…”
Section: The Hco + Emitting Heightmentioning
confidence: 99%
“…In this case, we may need to invoke an inner disk mass reservoir (e.g., dead zone) that can feed the star for a prolonged period of time with a low efficiency (Hartmann & Bae 2018). The presence of compact sub-millimeter continuum emission shown in ALMA observations (Long et al 2018;Keppler et al 2019) may support this inner reservoir scenario. Manara et al (2019) used the planet population synthesis models of Mordasini et al (2009Mordasini et al ( , 2012 to make predictions for stellar mass accretion rates and disk masses and compare them with observations of the Lupus and Chamaeleon star-forming regions.…”
Section: 2mentioning
confidence: 99%